Tapentadol prolonged release for patients with multiple myeloma suffering from moderate-to-severe cancer pain due to bone disease - Coluzzi F; Raffa RB; Pergolizzi J; Rocco A; Locarini P; Cenfra N; Cimino G; Mattia C (Journal of Pain Research, 2015)
Flaminia Coluzzi,1,2 Robert B Raffa,3 Joseph Pergolizzi,4 Alessandra Rocco,1 Pamela Locarini,1 Natalia Cenfra,5 Giuseppe Cimino,5 Consalvo Mattia1,2 1Department of Medical and Surgical Sciences and Biotechnologies, Faculty of Pharmacy and Medicine, Unit of Anaesthesiology, Intensive Care Medicine and Pain Therapy, Polo Pontino, Sapienza University of Rome, Latina, Italy; 2SIAARTI Study Group on Acute and Chronic Pain, Rome, Italy; 3Department of Pharmaceutical Sciences, Temple University School of Pharmacy, Philadelphia, PA, USA; 4Department of Medicine, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 5Department of Cellular Biotechnology and Hematology, Sapienza University of Rome, Rome, Italy Context: Myeloma bone disease (MBD) is a devastating complication of multiple myeloma that leads to severe pain. Objectives: The aim of this study was to evaluate the efficacy and tolerability of tapentadol prolonged release (PR) in the management of patients with MBD suffering from moderate-to-severe cancer pain. Methods: A 12-week prospective study was carried out in 25 opioid-naïve MBD patients. Patients initially received twice-daily doses of tapentadol PR 50 mg. Doses were then managed to maintain adequate relief or dose-limiting toxicity. The following parameters were recorded at weekly intervals for 4 weeks, and then at weeks 8 and 12: pain, opioid-related adverse effects, use of other analgesics, DN4 (Douleur Neuropathique 4) score. Quality of life (SF-36 [36-item short-form health survey]) was measured at baseline and at final evaluation. Results: Of 25 patients, 22 completed the study. Pain intensity significantly decreased from baseline to all the week intervals (P<0.01). Quality of life significantly improved with respect to all SF-36 subscale parameters (P<0.01), and so did both the physical and mental status (P<0.01). Tapentadol PR significantly reduced DN4 mean value (P<0.01) and the number of patients with neuropathic component (DN4 ≥4) (P<0.01). After 8 weeks of treatment, all patients were negative for the DN4 score. Tapentadol PR was well tolerated, and the use of other analgesics was reduced during the study period. Conclusion: Tapentadol PR started in doses of 100 mg/day was effective and well tolerated in opioid-naïve MBD patients with moderate-to-severe pain. Tapentadol PR can be considered a first-choice opioid in cancer patients suffering from mixed pain with a neuropathic component. Keywords: tapentadol, multiple myeloma, bone, neuropathic pain, opioids